Regulation and innovation in digital finance: The transformation of Latvia's banking sector - Ramona Rupeika-Apoga; Janis Priede; Gundars Berzins; Elmars Kehris (Digital Business, 2025)
The Latvian banking sector presents a policy and institutional puzzle: it maintains high loan interest rates despite low loan-to-deposit ratios and limited lending activity within the European Union. Anchored in credit rationing theory, this study investigates the institutional, regulatory, and technological factors influencing credit allocation. The examination is based on semi-structured interviews conducted with 29 senior experts and decision-makers from regulatory authorities, government ministries, and commercial banks, all of whom play a direct role in influencing Latvia's financial sector. Thematic analysis reveals constraints associated with regulatory-induced risk aversion, structural barriers to lending, borrower opaqueness and informality, the role of the state in facilitating lending, fintech integration challenges, and banking sector transformation. The findings demonstrate how compliance-driven institutional behavior, limited competition, and information asymmetries contribute to restricted lending. This study contributes to digital finance literature by showing how regulatory frameworks and institutional context in small EU economies influence the diffusion of financial innovation and credit access.
Keywords: 650; Banking; Competition; Interest rates; Latvia; Loans; State support programs